Intermarriage : its role and importance within early New Zealand shore whaling stations : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Owen, Emily V (Massey University, 2007)
Early contact history in New Zealand involved many hard working rugged European men who came to our shores to work as sealers, flax and timber traders as well as whalers, and their interaction with Māori who lived in and visited the areas which they frequented. It is the last of these men, the whalers who provide the context for this thesis. School history lessons and general New Zealand history books generally discuss whaling within New Zealand waters. Some provide enough information to give their audience a general understanding of some aspects of New Zealand's whaling history, while others contain so little that one might think that whaling had no impact on New Zealand's past. However this is not true; whaling had a significant impact in New Zealand's past and this impact has continued through to our contemporary society. Whaling had many consequences within early nineteenth century New Zealand, including the introduction of new commodities to Māori, such as tobacco, clothing, European tools and muskets which would all, to some extent, begin to change their traditional way of life. Interaction between whalers and local Māori brought on cultural changes. This interaction came in many forms, often through trade, but also the relationships between Māori women and European whalers. It is these relationships which are the focus of this thesis. Relationships between Māori women and European whalers started occurring when whaling ships began calling on New Zealand shores at the beginning of the nineteenth century. Often these relationships involved only fleeting encounters, but still they were the beginning of a trend which would, within the next forty years, see many shore whalers legally marry Māori women. This thesis deals with shore whalers who began to arrive in New Zealand during the late 1820s rather than the earlier deep sea whalers who called on Kororareka in the Bay of Islands. While deep sea whalers were the first to form relationships with Māori women they were in many respects different to shore whalers. Shore whalers were required to stay on shore for months at a time as opposed to a few days like deep sea whalers this meant they required different things from Māori they interacted with. This thesis will look at the relationships and marriages between European shore whalers from various locations along New Zealand's coastline and local women from the late 1820s through to 1845, discussing their role and importance within early New Zealand whaling stations.
Keywords: Interracial marriage; New Zealand -- History -- To 1840; Whalers (Persons); Women, Maori; Whalers' spouses; Whaling; New Zealand -- Social conditions